Perspektif Fiqh Siyasah Tanfidziyyah terhadap Penutupan Stasiun Lambuang Kota Bukittinggi - Rifky Setiawan; Helfi Helfi (Lembaga Yasin AlSys, 2026)
This study was motivated by the policy of the Bukittinggi City Government to close Lambuang Station as an effort to safeguard regional finances and optimize asset management, which had previously imposed a rental burden payable to PT Kereta Api Indonesia (PT KAI). This study aims to analyze the policy of closing Lambuang Station and examine it from the perspective of fiqh siyasah tanfidziyyah. This study used field research with a qualitative approach. Data were collected through interviews, observation, and documentation. The results showed that the closure of Lambuang Station was a local government policy directed at realizing public welfare through regional financial efficiency and the optimization of public assets. From the perspective of fiqh siyasah tanfidziyyah, this policy can be justified because it is in line with the principle of public welfare and the protection of public wealth (hifz al-mal). However, the implementation of the policy still needs to consider the principles of justice and the economic rights of affected communities. Thus, this study affirms that public policy in the management of regional assets should not only be oriented toward administrative and fiscal efficiency but also consider the values of public welfare, justice, and the protection of community interests.